If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + 3y) = 3y + 6x (2x * -3 + 3y * -3) = 3y + 6x (-6x + -9y) = 3y + 6x Reorder the terms: -6x + -9y = 6x + 3y Solving -6x + -9y = 6x + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6x + -6x + -9y = 6x + -6x + 3y Combine like terms: -6x + -6x = -12x -12x + -9y = 6x + -6x + 3y Combine like terms: 6x + -6x = 0 -12x + -9y = 0 + 3y -12x + -9y = 3y Add '9y' to each side of the equation. -12x + -9y + 9y = 3y + 9y Combine like terms: -9y + 9y = 0 -12x + 0 = 3y + 9y -12x = 3y + 9y Combine like terms: 3y + 9y = 12y -12x = 12y Divide each side by '-12'. x = -1y Simplifying x = -1y
| (x+1)(x-1)(x-9)=0 | | X-9x=70 | | 2p-9=4p | | 5(15x+20)+9x(30)=78 | | k-14=29 | | 3/5(5x+10)=5/6(12x-18) | | m/11=9 | | 4a+4/5=-4 | | (X-7)+(2x+1)=180 | | 56x^2+53x+12=0 | | 6(k+4)=8k+2 | | w+2=3w+16 | | 3(u-5)-5u=11 | | 7y^2+19y+10= | | x^2+17/9x=25 | | ((3x+6)/(5x^2))((x)/(x^2-4)) | | 7x+(-12/5+2/5)=-8 | | -4x^3+4x^2+3x=0 | | .5x-8=2x+7 | | 0.35x+500=2.5x | | 5y^2-3y-2= | | -5y=-2x+7 | | P(7)=10(7)-7 | | 6+5(3k+4)=146 | | (2x-9)(2x-9)= | | 3+(18-2x(3+4)+1)= | | 5/2x=-40 | | 3a+1b=27 | | 6=10z | | 25.4/275 | | 275/25.4 | | 8.7*1.4= |